Cell retention in scalable, perfusion-based mesenchymal stem cell expansion processes: a proof of concept - Schneider, Samuel Lukas; Gopalakrishnan, Abiram; Teale, Misha Alexander; Eibl, Regine (Frontiers in Bioengineering and Biotechnology, 2025)
The production of clinically relevant quantities of human mesenchymal stromal cells (hMSCs) requires scalable and intensified manufacturing processes. For this reason, the applicability of alternating tangential flow filtration (ATF) and tangential flow depth filtration (TFDF) based cell retention systems for hMSC expansion on microcarriers (MCs) in perfusion mode was assessed. The processes were conducted in stirred tank bioreactors at a scale of 1.8 L and compared with repeated-batch cultivations. In the perfusion and repeated-batch control cultivations, competitive viable cell concentrations of ≈2.9 · 106 cells mL−1 were reached within a cultivation period of 5–7 days, resulting in an expansion factor of 41–57. The main difference between the operation modi was the aggregation behavior of the MCs. While the median MC aggregate diameter in the repeated-batch cultivation reached 470 μm, the ATF cell retention device constrained aggregate size to a median diameter of 250 µm. In the TFDF cultivation, the shear forces in the recirculation loop stripped most of the hMSCs from the MCs, resulting in the formation of spheroids that continued to proliferate, albeit at a decreased rate. While perfusion operation did not lead to increased productivity in this proof-of-concept study, manual handling and therefore contamination risk were reduced by replacing the repeated-batch process’s daily 80% medium exchanges with automated perfusion operation. Additionally, the ATF system was shown to be useful for medium removal and washing of the MCs prior to adding the harvesting solution, which is highly valuable for cultivations conducted at larger scales. While the feasibility of ATF based cell retention for MC expansion processes could be demonstrated, increased growth area to medium ratios, i.e., higher MC concentrations, still need to be investigated to leverage the full potential of the perfusion process mode.